Morphometric Traits, Serum Chemistry and Antibody Response of Three Chicken Genotypes under Free-Range, Semi-Intensive and Intensive Housing Systems - Ahmad,S (2019)
ABSTRACT The present study evaluated the effect of housing system on the morphometrics, serum chemistry and antibody response of dual-purpose chicken genotypes. A total of 156 pullets and 39 cockerels were randomly picked from 18 treatment block groups (3 housing system × 3 genotypes × 2 sexes) according to Randomized Complete Block Design (RCBD). Three genotypes, purebred Naked Neck (NN) and two crossbred Rhode Island Red × Naked Neck (RIR × NN = RNN) and Black Australorp × Naked Neck (BAL × NN = BNN), were compared. Morphometric traits were recorded during rearing period, thereafter, serum chemistry and antibody response were evaluated in pullets. Intensive and semi-intensive chickens were heavier (males, p=0.0012; females, p<0.0001) on week 21. Body length was maximum (p<0.0001) for free-range female chicken. Maximum (p<0.0001) keel length was found in semi-intensive female chickens. Regarding genotypes, RNN and BNN chickens were heavier than NN (males, p=0.0015; females, p<0.0001). Keel length was maximum (p=0.0002) in BNN and NN female chickens. Drumstick circumference were maximum (males, p<0.0001; females, p<0.0001) in NN chickens, shank circumference was maximum (p=0.0150) in RNN and BNN male chickens. Wingspan was maximum (p=0.0029) in NN female chickens. Plasma glucose level was higher (p=0.0008) in intensive female chickens whereas cholesterol levels was higher (p=0.0123) in NN female chicken. Antibody titer against ND was higher (p=0.0204) in RNN female chickens while higher (p=0.0001) antibody titer against IB was found in free-range chickens. Overall, housing system did not impact morphometric traits or serum chemistry. Only a few differences were observed regarding body weight, body and keel length, plasma glucose, cholesterol and antibody response against ND and IB.